Persepsi Masyarakat Terhadap Buruh Tani Perempuan Di Desa Wuwuk Kecamatan Tareran Kabupaten Minahasa Selatan - Lengkong, Gabriela Melisa; Pangemanan, Paulus Adrian; Kaunang, Rine (AGRI-SOSIOEKONOMI, 2023)
This study aims to describe people's perceptions of female farm laborers in Wuwuk Village, Tareran District, South Minahasa Regency. The research was conducted from May to July 2023. The data used in this study were primary data and secondary data. Primary data was obtained from direct interviews with 25 respondents who are the general public of Wuwuk Village. Secondary data obtained from literature studies, libraries, and journals. The sampling technique in this study is purposive sampling technique. The data analysis method used is descriptive analysis. The results of the study show that the people of Wuwuk Village on average agree with women's work as farm laborers because according to the community work as farm laborers is work that not only men but also women can do. The Wuwuk Village community considers that the women farm workers in Wuwuk Village are tough women whose energy and performance are not inferior to men, and there are even women whose energy and performance are better than men. However, there are also people who disagree with women's work as farm laborers because according to the community work as farm laborers is not suitable for women, they argue that women should focus on household activities.